Groundwater evolution and mean water age inferred from hydrochemical and isotopic tracers in a tropical confined aquifer. Issue 14 (20th June 2018) - Villegas, Pedro; Paredes, Vanesa; Betancur, Teresita; Taupin, Jean D.; Toro, Luis E.
Abstract: The coastal confined aquifer in the Gulf of Urabá (Colombia) is an important water source for the banana agro‐industry as well as for urban and rural communities. However, the main processes controlling recharge and mixing in the aquifer are still poorly understood. Hydrochemical analyses and stable isotope monitoring were conducted to (a) determine groundwater recharge origin, mean groundwater age, and the main processes governing groundwater chemistry and the potential mixing of marine water and the influence of diffusive processes from the two surrounding aquitard layers. Hydrochemical data indicate that the main processes affecting the dissolved chemical composition include cation exchange, dissolution of carbonated and CO2, and silicate weathering. δ 18 O and δ 2 H compositions combined with 14 C data highlight the differences in climatic conditions between the recharge zone and the confined section of the aquifer, which is close to the Atlantic Ocean. Groundwater samples with 14 C ages from recent to 28, 300 years BP show a depleted isotopic trend ranging from −6.43‰ to −9.14‰ in δ 18 O and from −43.2‰ to −65.7‰ in δ 2 H. The most depleted δ 18 O and δ 2 H compositions suggest a cooler recharge climate than the current conditions (corresponding to the last glacial period of the late Pleistocene). Depleted δ 13 C values in the total dissolved inorganic carbon indicate the existence of organic material oxidation processes within the geologic formation. These results can be used or transferred to enhance groundwater modelling efforts in other confined coastal aquifers of South America where scarcity of long‐term monitoring data limits water resources planification under a changing climate.